(untitled) (American Journal of Islam and Society, 1987)
Akbar S. Ahmed, Toward Islamic Anthropology: Definition, Dogma, and Directions, Islamization of Knowledge series (2) New Era Publications/International Institute of Islamic Thought 1976, 77 pp. Talal Asad, The Idea of an Anthropology of Islam, Center for contemporary Arab studies, Georgetown University, Washington, D.C. 1986, 22 pp. I. The Malaise and its Remedy Both of these scholarly publications may be seen as statements of the need for Islamic anthropology. They contain expressions of the discontent of Muslin anthropologists with the state of the art of contemporary anthropological studies. Many Muslim anthropologists and other social scientists share in the feelings evident in these essays and well stated in the late Dr. Ali Shari’ati’s Civilization and modernization: When I feel my own religion, literature, emotion, needs and pains through my awn culture, I feel my own self, the very social and historical ...